Vitamin E inhibits CD36 scavenger receptor expression in hypercholesterolemic rabbits - KARTAL ÖZER, NESRİN (ELSEVIER IRELAND LTD, 2006)
A numerous studies suggest that Vitamin E has a preventive role in atherosclerosis, although the mechanism of action still remains unclear. CD36, a member of the scavenger receptor family is centrally involved in the uptake of oxidized low density proteins (oxLDLs) from bloodstream. During the atherosclerotic process, the lipid cargo of oxLDL accumulates in macrophages and smooth muscle cells, inducing their pathological conversion to foam cells. In the present study, we investigate the role of Vitamin E on CD36 expression in an in vivo model. Atherosclerosis was induced by a 2% cholesterol containing Vitamin E poor diet. Three groups of six rabbits each were studied. The first group (control) was fed on Vitamin E poor diet. The second group was fed with Vitamin E poor diet containing 2% cholesterol and the rabbits in the third group were fed with Vitamin E poor diet containing 2% cholesterol and received injections of 50 mg/kg of Vitamin E i.m. After 4 weeks, aortas were removed and analysed by light microscopy for atherosclerotic lesions. Aortic samples were analysed for CD36 mRNA expression. The aortas of cholesterol-fed rabbits showed typical atherosclerotic lesions, detected by macroscopic and microscopic examination, and exhibited an increase in CD36 mRNA expression. Vitamin E fully prevented cholesterol induced atherosclerotic lesions and the induction of CD36 mRNA expression. The effects observed at the level of CD36 scavenger receptor expression in vivo suggest an involvement of reduced foam cell formation in the protective effect of Vitamin E against atherosclerosis. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: atherosclerosis; CD36; scavenger receptor; vitamin E; alpha-tocopherol; rabbit aortic smooth muscle cells; ALPHA-TOCOPHEROL DECREASES; LOW-DENSITY LIPOPROTEINS; CORONARY-HEART-DISEASE; SMOOTH-MUSCLE-CELLS; PROTEIN-KINASE-C; E CONSUMPTION; OXIDIZED LDL; ATHEROSCLEROSIS; CHOLESTEROL; ANTIOXIDANT